Governance in Africa conversations - Mo Ibrahim Foundation (London : centre of African Studies, 2011)
The governance in Africa conversations series are produced as 30 min ute radio shows aimed at audiences in the African continent. They are a lso recorded in video format for online distribution and as educational resources for universities in Africa. These audio and video programmes are available for broadcasting and syndicating free of charge through national and community radio and TV stations.
DVD 1 series features Jibrin Ibrahim the director ofthe Centre for d emocracy and development, Daniel Kaufmann, and Simon Kolawole. DVD 2 fe atures Luisa Diogo the former prime minister of Mozambique, Stephen Cha n and Hein Marais, the writer and journalist and former deputy editor o f work in progress magazine of South africa and former chief writer for the UN pro.
The series governance in Africa conversations brings together some o f the most important and inspired thinkers and experts focusing on issu es affecting governance in Africa.
DVD ROM.
This series features two parts each stored on a separate DVD
English.
Keywords: Political leadership -- Africa